Evaluation of a Campylobacter jejuni N-glycan-ExoA glycoconjugate vaccine to reduce C. jejuni colonisation in chickens. Issue 51 (17th December 2021) - Vohra, Prerna; Chintoan-Uta, Cosmin; Bremner, Abi; Mauri, Marta; Terra, Vanessa S.; Cuccui, Jon; Wren, Brendan W.; Vervelde, Lonneke; Stevens, Mark P.
Abstract: Campylobacter jejuni is the leading bacterial cause of human gastroenteritis worldwide and handling or consumption of contaminated poultry meat is the key source of infection. Glycoconjugate vaccines containing the C. jejuni N -glycan have been reported to be partially protective in chickens. However, our previous studies with subunit vaccines comprising the C. jejuni FlpA or SodB proteins with up to two or three C. jejuni N -glycans, respectively, failed to elicit significant protection. In this study, protein glycan coupling technology was used to add up to ten C. jejuni N -glycans onto a detoxified form of Pseudomonas aeruginosa exotoxin A (ExoA). The glycoprotein, G-ExoA, was evaluated for efficacy against intestinal colonisation of White Leghorn chickens by C. jejuni strains M1 and 11168H relative to unglycosylated ExoA. Chickens were challenged with the minimum dose required for reliable colonisation, which was 10 2 colony-forming units (CFU) for strain M1 and and 10 4 CFU for strain 11168H. Vaccine-specific serum IgY was detected in chickens vaccinated with both ExoA and G-ExoA. However, no reduction in caecal colonisation by C. jejuni was observed. While the glycan dose achieved with G-ExoA was higher than FlpA- or SodB-based glycoconjugates that were previously evaluated, it was lower than that of glycoconjugates where protection against C. jejuni has been reported, indicating that protection may be highly sensitive to the amount of glycan presented and/or study-specific variables.